Roles for multifunctional and specialized spinal interneurons during motor pattern generation in tadpoles, zebrafish larvae, and turtles - Berkowitz, Ari; Roberts, Alan; Soffe, Stephen R. (Frontiers in Behavioral Neuroscience, 2010)
The hindbrain and spinal cord can produce multiple forms of locomotion, escape, and withdrawal behaviors and (in limbed vertebrates) site-specific scratching. Until recently, the prevailing view was that the same classes of CNS neurons generate multiple kinds of movements, either through reconfiguration of a single, shared network or through an increase in the number of neurons recruited within each class. The mechanisms involved in selecting and generating different motor patterns have recently been explored in detail in some non-mammalian, vertebrate model systems. Work on the hatchling Xenopus tadpole, the larval zebrafish, and the adult turtle has now revealed that distinct kinds of motor patterns are actually selected and generated by combinations of multifunctional and specialized spinal interneurons. Multifunctional interneurons may form a core, multipurpose circuit that generates elements of coordinated motor output utilized in multiple behaviors, such as left-right alternation. But, in addition, specialized spinal interneurons including separate glutamatergic and glycinergic classes are selectively activated during specific patterns: escape-withdrawal, swimming and struggling in tadpoles and zebrafish, and limb withdrawal and scratching in turtles. These specialized neurons can contribute by changing the way central pattern generator (CPG) activity is initiated and by altering CPG composition and operation. The combined use of multifunctional and specialized neurons is now established as a principle of organization across a range of vertebrates. Future research may reveal common patterns of multifunctionality and specialization among interneurons controlling diverse movements and whether similar mechanisms exist in higher-order brain circuits that select among a wider array of complex movements.